2009
DOI: 10.1002/gps.2233
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety does not predict response to antidepressant treatment in late life depression: results of a meta‐analysis

Abstract: In randomized, placebo-controlled trials, anxiety in late-life depression was not associated with decreased response to second generation antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 25 publications
1
22
3
Order By: Relevance
“…Further, their co-occurrence was associated with long-standing vulnerability (a personal history of anxiety or depression) to affective disorders, and a study by Steffens and McQuoid [8] showed that depressed patients with anxiety symptoms had worse short-term outcomes than patients without anxiety symptoms. These results are uncertain, as Nelson et al [9] found no significant differences between the outcomes of antidepressant treatment in depressed patients with or without anxiety. Thus, the consequences on symptom level or illness outcome of comorbid anxiety in depressed patients are to be explored.…”
Section: Introductioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Further, their co-occurrence was associated with long-standing vulnerability (a personal history of anxiety or depression) to affective disorders, and a study by Steffens and McQuoid [8] showed that depressed patients with anxiety symptoms had worse short-term outcomes than patients without anxiety symptoms. These results are uncertain, as Nelson et al [9] found no significant differences between the outcomes of antidepressant treatment in depressed patients with or without anxiety. Thus, the consequences on symptom level or illness outcome of comorbid anxiety in depressed patients are to be explored.…”
Section: Introductioncontrasting
confidence: 40%
“…The effect of antidepressants would be similar in depressed patients with or without anxiety, as described by Nelson et al [9]. Since the patients were hospitalized in spite of this treatment, one might speculate whether anxiolytics had an insufficient effect on anxiety symptoms, either because the dosage was inadequate or because this class of drugs had no effect.…”
Section: Discussionmentioning
confidence: 78%
“…No Yes Nelson 2009 In randomized, placebo-controlled trials, anxiety in late-life depression was not associated with decreased response to second generation antidepressants…”
Section: No No Yesmentioning
confidence: 98%
“…In mixed-aged samples, female sex was associated with better global outcome in open-label studies (34), but male sex was associated with greater drug-placebo differences (35). Open-label studies of late-life depression have found that anxious depression predicts poorer global outcome (36,37), but a trial-level meta-analysis found that anxious depression was not associated with lower drug-placebo differences in older depressed patients (38). Impaired cognition has also received attention.…”
mentioning
confidence: 97%